Dam Break Analysis Berdasarkan Skenario Overtopping Menggunakan Aplikasi HECRAS 2D pada Bendungan Leuwikeris - Muhammad Dhaffa Firmansyah; S. Kamilia Aziz (Jurnal Aplikasi Teknik Sipil, 2025)
Dams have benefits derived from large water reservoirs as a source of water. The larger the water source being stored, the greater the potential risk to communities downstream due to the failure or collapse of the dam structure. The majority of earth-fill dams experience collapse 35% of the time due to overtopping. Based on flood tracking, the Leuwikeris Dam experienced overtopping at +160.351. Collapse simulations of the dam were conducted using HEC-RAS 2D with the collapse parameter equations from the Froehlich 2008 method. The simulation results indicate that the dam collapse resulted in flooding covering an area of 189.2581 km²downstream of the Leuwikeris Dam